2004
DOI: 10.3928/0147-7447-20040401-15
|View full text |Cite
|
Sign up to set email alerts
|

Medial Collateral Ligament "Tibial" Injuries: Indication for Acute Repair

Abstract: Complete avulsions of the superficial and deep medial collateral ligament from the tibia with disruption of the meniscal coronary ligament should be managed with acute surgical repair for maximum benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…An avulsion of the MCL from the distal tibial insertion is 1 such example. 4 , 9 , 10 , 11 , 12 Unfortunately, the majority of literature discussing nonoperative and surgical management of MCL injuries does not distinguish the site of ligamentous injury, making the true incidence and associated treatment outcomes of distal injuries difficult to discern. Nevertheless, there is evidence to suggest that distal tibial MCL injuries do not do well with conservative management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An avulsion of the MCL from the distal tibial insertion is 1 such example. 4 , 9 , 10 , 11 , 12 Unfortunately, the majority of literature discussing nonoperative and surgical management of MCL injuries does not distinguish the site of ligamentous injury, making the true incidence and associated treatment outcomes of distal injuries difficult to discern. Nevertheless, there is evidence to suggest that distal tibial MCL injuries do not do well with conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in 2004, Wilson et al. 12 reported that a number of athletes had failed conservative management of grade III MCL injuries. These athletes were found to have complete detachments of the distal MCL from the tibia requiring delayed surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of complete grade III injuries depends on whether the injuries are isolated or combined with other liga- 13 Surgery should be considered in certain circumstances: acute superficial MCL injuries in which the tibial insertion is displaced outside the pes anserinus tendons (Stener lesion), chronic laxity and instability after nonoperative treatment of isolated grade III injuries, multiligament injuries and knee dislocations, and some cases of MCL instability in the valgus aligned knee. Numerous reconstruction techniques exist for surgical treatment of grade III injuries, including combined repair and reconstruction, superficial MCL reconstructions, and MCL and POL reconstructions.…”
Section: Treatmentmentioning
confidence: 99%
“…Surgery is recommended when injury is over the whole length of the superficial layer of the MCL or when there is injury to both the superficial and deep layers of the MCL. 17 18 19 …”
mentioning
confidence: 99%